Job Satisfaction of Female Faculty in Arts and Science Colleges in Coimbatore District - Sumath, V; Velmurugan, R (International Journal of Engineering and Technology, 2018)
Productive contribution of teachers towards institution and student development depends on not only their educational qualification and experience but also their job satisfaction. Satisfied teachers will contribute more towards institution and student enrichment.Â  So, it is the duty of management of educational institutions to keep their faculty satisfied for their long-term survival. In this study an earnest attempt has been made to ascertain the factors influencing job satisfaction of women staff members working at Arts and Science Colleges in Coimbatore District. The result of the study portrays that women faculty are satisfied with regard to recognition received from their superiors followed by revision of salary (Ausekar, 1996), salary offered (Sharma, 2005), increment offered by the management for acquiring additional educational qualification etc.Â Â